POPULATION DYNAMICS AND STOCK ASSESSMENT OF KOTH (OTOLITHOIDES BIAURITUS, CANTOR, 1850) ALONG THE NORm-WEST COAST OF INDIA - KUMAR, P.P. MANOJ; ACHARYA, P.; GULATI, D. (Journal of Indian Fisheries Association, 2015)
MSY, groÂ·wth, selection and mortality parameters of Otolitlwitles hiauritus have beenworked out from data collected by MFV Saraswati of CIFE, and length frequency data fromFerry Wharf, Sasson dock, and Versova fish landing centres of Bombay. Values of Loc, K,and to obtained fmm lenght ftÂ·cquency study are 1572mm, 0.2633/yr and 0.0289 yr respectively,and of weight grmvth parameters are Woc = 10067g, K= 0.03904/yr and to = 0.0137yr.Selection parameters arc Lr + 150mm, tr + 0.4167 yr lc + 240mm and tc = 0.6367yr. Selectionfactor (K) for codend worked out to be 12. Based on Z=0.6486, the MSY of Otolitlwidesbiauritus off nOiihl\'est coast of India is assessed as 1,802 tons. which is slightly higher thanthe current catch level of 1,634 tons.